Sexual orientation and gender identity - Healey, Justin (Issues in society (Balmain, N.S.W.) ;, 2014)
Sexual orientation and gender identity are separate, distinct parts of people's overall identity. Equality and freedom from discrimination are human rights belonging to all people, however, lesbian, gay, bisexual, trans, gender diverse and intersex (LGBTI) people experience harassment and hostility in many areas of everyday life. Under recently enacted Australian law it is illegal to discriminate against a person on the basis of sexual orientation, gender identity and intersex status. Same-sex couples are now also protected from discrimination under the definition of "marital or relationship status". This book explores issues involving sexual orientation, gender diversity and intersex status; and explains what equality means for people who are often subjected to misunderstanding and homophobia